2007
DOI: 10.1007/s10562-007-9049-1
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of low temperature induced SMSI on Pd/TiO2 catalysts

Abstract: Pd/TiO 2 catalysts were found to enter an strong metal support interaction (SMSI) state after reduction at temperatures as low as 473 K. This was identified as a significant loss in the CO uptake as monitored by low temperature FTIR. Electron microscopy provides direct evidence of the presence of ordered, reduced titanium oxide layers over palladium (SMSI state) for Pd/TiO 2 catalysts following reduction at temperature 623 K. The crystal phase was identified as Ti 4 O 7 and this phase, once formed, was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…In the case of Pd-and Pt-loaded TiO 2 , a detrimental effect was observed by increasing the reduction temperature, which may be attributed to metal particle sintering, as confirmed by the increase in the dimensions of the metal nanoparticles (d M ) determined by TEM, especially in the case of Pt-TiO 2 ( Table 2). For Pd/TiO 2 the loss of activity can also be attributed to a strong metal support interaction (SMSI) effect, as previously reported in the literature for this type of catalyst [39][40][41]. Sá et al have reported the occurrence of reduced titanium oxide layers over palladium (SMSI state) for reduction temperatures above 623 K [39].…”
Section: Effect Of the Nature And Reduction Temperature Of The Cocatasupporting
confidence: 58%
See 1 more Smart Citation
“…In the case of Pd-and Pt-loaded TiO 2 , a detrimental effect was observed by increasing the reduction temperature, which may be attributed to metal particle sintering, as confirmed by the increase in the dimensions of the metal nanoparticles (d M ) determined by TEM, especially in the case of Pt-TiO 2 ( Table 2). For Pd/TiO 2 the loss of activity can also be attributed to a strong metal support interaction (SMSI) effect, as previously reported in the literature for this type of catalyst [39][40][41]. Sá et al have reported the occurrence of reduced titanium oxide layers over palladium (SMSI state) for reduction temperatures above 623 K [39].…”
Section: Effect Of the Nature And Reduction Temperature Of The Cocatasupporting
confidence: 58%
“…For Pd/TiO 2 the loss of activity can also be attributed to a strong metal support interaction (SMSI) effect, as previously reported in the literature for this type of catalyst [39][40][41]. Sá et al have reported the occurrence of reduced titanium oxide layers over palladium (SMSI state) for reduction temperatures above 623 K [39].…”
Section: Effect Of the Nature And Reduction Temperature Of The Cocatasupporting
confidence: 58%
“…Indeed, the elevated temperature and reducing conditions employed in hydrogenation reactions can in principle present another stability challenge for reducible oxides such as TiO 2 . Such supports can suffer from noble‐metal mediated H spillover onto the support, resulting in surface reduction and support rearrangement and ultimately coverage of the metal nanoparticle by the support, a phenomenon described as Strong Metal Support Interaction (SMSI) . The SMSI concept was first developed by Tauster et al .…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated with FT‐IR that reduced CO uptake due to SMSI was already seen for Pd/TiO 2 catalyst after H 2 reduction at 200 °C. Upon increasing the reduction temperature to 350 °C, patches of a Ti 4 O 7 phase on the Pd particles could be observed by TEM . In addition to high temperature H 2 reduction, surface decoration can also occur by vacuum treatment, for which, again, high temperatures are needed (e. g. 327–527 °C) ,,…”
Section: Introductionmentioning
confidence: 99%
“…CO oxidation is a typical catalytic reaction [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Model catalysis and theoretical calculation reveal that CO oxidation on Pt-group metals follows the LangmuirHinshelwood (L-H) reaction mechanism [5-12, 16, 18-20].…”
Section: Introductionmentioning
confidence: 99%